Advances in the study of LNPs for mRNA delivery and clinical applications - Wang, Bili; Shen, Biao; Xiang, Wenqing; Shen, Hongqiang (Virus genes, 2024)
Messenger ribonucleic acid (mRNA) was discovered in 1961 as an intermediary for transferring genetic information from DNA to ribosomes for protein synthesis. The COVID-19 pandemic brought worldwide attention to mRNA vaccines. The emergency use authorization of two COVID-19 mRNA vaccines, BNT162b2 and mRNA-1273, were major achievements in the history of vaccine development. Lipid nanoparticles (LNPs), one of the most superior non-viral delivery vectors available, have made many exciting advances in clinical translation as part of the COVID-19 vaccine and therefore has the potential to accelerate the clinical translation of many gene drugs. In addition, due to these small size, biocompatibility and excellent biodegradability, LNPs can efficiently deliver nucleic acids into cells, which is particularly important for current mRNA therapeutic regimens. LNPs are composed cationic or pH-dependent ionizable lipid bilayer, polyethylene glycol (PEG), phospholipids, and cholesterol, represents an advanced system for the delivery of mRNA vaccines. Furthermore, optimization of these four components constituting the LNPs have demonstrated enhanced vaccine efficacy and diminished adverse effects. The incorporation of biodegradable lipids enhance the biocompatibility of LNPs, thereby improving its potential as an efficacious therapeutic approach for a wide range of challenging and intricate diseases, encompassing infectious diseases, liver disorders, cancer, cardiovascular diseases, cerebrovascular conditions, among others. Consequently, this review aims to furnish the scientific community with the most up-to-date information regarding mRNA vaccines and LNP delivery systems.